2015
DOI: 10.1016/j.ijsbe.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Household energy consumption and carbon emissions for sustainable cities – A critical review of modelling approaches

Abstract: 11The purpose of this paper is to conduct a review of how household energy consumption and carbon emissions (HECCE) modelling 12 paradigms have evolved over the years. This is achieved by adopting the literature review methodology for the study. The paper first 13 reviewed the previous studies that are serving as the theoretical framework underpinning the HECCE models. Further to this, the paper 14 identified an array of energy models that have evolved over the years together with their capability of analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…HSEMs poorly describe the influence of occupants and their behaviour on energy demands [30], likewise local climatic conditions [74]. In previous reviews of HSEMs [12,74,105], a set of performance gaps have been identified. The first set is related to data resolution: a) a reliance on iso-…”
Section: Decision Making In Hsemsmentioning
confidence: 99%
“…HSEMs poorly describe the influence of occupants and their behaviour on energy demands [30], likewise local climatic conditions [74]. In previous reviews of HSEMs [12,74,105], a set of performance gaps have been identified. The first set is related to data resolution: a) a reliance on iso-…”
Section: Decision Making In Hsemsmentioning
confidence: 99%
“…Energy models created with a bottom-up approach can be divided into Building Physics Model and Statistical Model [9][10][11].…”
Section: Phase 2: Model Design and Detailed Analysismentioning
confidence: 99%
“…This model tries to predict behaviour as a result of a variety of predictors that determine a person's intention towards a specific behaviour. This framework is widely used in many different fields of pro-environmentalist, occupant and consumer behaviour and in building energy research fields as well (Chen and Knight 2014) ) (Gao et al 2016) (Oladokun and Odesola 2015) (Staddon et al 2016). Schwartz and Bilsky defined values as beliefs pertaining to desirable end states or mode of conduct that transcend specific situations and guide choices and actions (Schwartz and Bilsky 1990).…”
Section: Behavioural Models and Studies From Social Sciencesmentioning
confidence: 99%